The stones still shout sensational highlights of the Bible and archaeology - Wilson, Clifford A., 1923-; Wilson, Barbara (Boronia, VIC Pacific Christian Ministries, 1999)
Includes bibliographical references and indexes.
Keywords: Bible -- archaeology